PERSENTASE BOBOT KARKAS AYAM PEDAGING SETELAH PEMBERIAN BERBAGAI DOSIS MINYAK BUAH MERAH (Pandanus Conodeus. lam) - Untung Untung (Universitas Halu Oleo, 2016)
This study was designed using a complete randomized design (RAL) with four treatments and each treatment was repeated as many as 5m (five) times to obtain 20 experimental units, each experimental unit consisting of 5 (five) chickens. The tested treatment was giving various doses of red fruit oil with the application of mouth drops. The given dose is 0 cc / tail (0 drops), 0.05 cc / tail (1 drop), 0.1 cc / head (2 drops), and 0.15 cc / tail (3 drops). Red (Pandanus Conodeus Lam) dose of 0.15 cc (3 drops) increased live weight gain and best carcass weight at week V and significantly different from control treatment and 0.05 cc / head. Provision of 0.15 cc red fruit oil (3 drops) resulted in live weight of 2.046 kg / head, carcass weight of 1,462 kg and percentage of carcasses 71%. Key Words : Red Fruits (Pandanus Conodeus. lam), Broiler, Weight of carcasses